A three-phase power flow algorithm for ungrounded network based on constraints of zero-sequence components. (February 2023) - Zhang, Yi; Lin, Jinrong; Li, Chuandong
Highlights: The paper constrains the zero-sequence currents of the ungrounded winding nodes to zero, and combines with the power equations and the Newton Raphon method to propose a three-phase power flow algorithm for ungrounded distribution networks. The paper analyzes (a) the convergence problem of the method that constrains squares of zero-sequence voltages and currents to zero based on mathematical derivation and (b) the inapplicability problem of the method that constrains zero-sequence voltages to zero of the ungrounded winding nodes based on both a theoretical analysis and verification by examples. The algorithm proposed in the paper is universally applicable, and has a low computation time, high efficiency and good convergence performance. It has the potential to be widely applicable to engineering practice. Abstract: The existing research on three-phase power flow in ungrounded distribution networks primarily adopts the methods of presetting zero-sequence reference voltages and neutral point reference voltages. This makes it impossible to calculate the power flow in ungrounded network with non-zero neutral point voltages or zero-sequence voltages. Furthermore, a unified zero-sequence components constraint method of ungrounded distribution network does not exist. In this paper, a three-phase power flow algorithm is proposed to calculate three-phase power flow in an ungrounded distribution network. First, power flow equation variables, transformer admittance matrices and zero-sequence components are used to analyze the characteristic of three-phase power flow in an ungrounded distribution network. Second, a three-phase power flow algorithm for ungrounded distribution network is designed by constraining the zero-sequence currents of the ungrounded winding nodes to zero. Third, theoretical analyses and mathematical derivations are used to prove the applicability of the two methods, one of which constrains zero-sequence voltages of ungrounded winding nodes to zero and the other constrains squares of zero-sequence voltages and currents to zero. Last, a five-nodes network, modified IEEE123 network and practical network are used to demonstrate that the proposed method has a high accuracy and good applicability in calculating the three-phase power flow of ungrounded distribution networks.